Work Culture, Information Technology, and Employee Performance: The Mediating Role of Work Discipline - Sri Oktavianti; Betti Nuraini; Ronal Aprianto; Herman Paleni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to empirically examine the influence of work culture and information technology on employee performance, with work discipline as a mediating variable at the Department of Communication, Informatics, Statistics, and Encryption of Lubuklinggau City. The research was conducted at the aforementioned department, addressing issues such as the lack of data-based evaluations of program effectiveness, which hinders optimal service improvement; a lack of responsibility in task completion, leading to delays in program and public service implementation; and limited bandwidth causing slow internet connectivity. The population in this study consists of all employees at the Department of Communication, Informatics, Statistics, and Encryption of Lubuklinggau City. The sample includes 47 respondents from the same department. This is a quantitative study employing the Structural Equation Modeling (SEM) method using SmartPLS 4.0 software. The results show that work culture and information technology, both partially and simultaneously, have a significant effect on employee performance. Additionally, work culture and information technology also influence work discipline, both individually and collectively. Furthermore, work culture and information technology, mediated by work discipline, significantly impact employee performance.